Application of calcium-to-phosphorus (Ca/P) ratio in the diagnosis of pseudohypoparathyroidism: another piece in the puzzle of diagnosis of Ca-P metabolism disorders - De Vincentis, Sara; Del Sindaco, Giulia; Pagnano, Angela; Brigante, Giulia; Moretti, Antonio; Zirilli, Lucia; Rochira, Vincenzo; Simoni, Manuela; Mantovani, Giovanna; Madeo, Bruno (Frontiers in Endocrinology, 2023)
Objective: The serum calcium/phosphorus (Ca/P) ratio has been proposed to identify patients with primary hyperparathyroidism and chronic hypoparathyroidism (HPT), but it has never been tested in pseudohypoparathyroidism (PHP). The aim of this study was to test the performance of Ca/P ratio in PHP diagnosis compared to healthy subjects and HPT patients for differential diagnosis.Design: Retrospective, cross-sectional, observational study. Methods: Serum Ca, P, creatinine, parathyroid hormone (PTH), and albumin were collected. Ca and P were expressed in mmol/L. Ca/P diagnostic performance was evaluated by receiver operating characteristic (ROC) curve, sensitivity, specificity and accuracy.Results: A total of 60 PHP, 60 HPT patients and 120 controls were enrolled. The Ca/P ratio was lower in PHP and HPT patients than controls (p<0.0001). The cut-off of 1.78 (2.32 if Ca and P measured in mg/dL) for Ca/P ratio could identify PHP and HPT patients among the entire cohort (sensitivity, specificity: 76%). No valid cut-off of Ca/P was found to discriminate PHP from HPT patients; in this case, PTH above 53.0 ng/dL identified PHP patients (sensitivity, specificity: 100%). The index (Ca/P x PTH) above 116 ng/L recognized PHP patients from controls (sensitivity 84.7%; specificity 87.4%), whereas (Ca/P x PTH) below 34 ng/L recognized HPT patients from controls (sensitivity 88.9%; specificity 90.8%).The Ca/P ratio below 1.78 (2.32 CU) is highly accurate to identify PHP and HPT patients, while it is not reliable to differentiate these two conditions. The index (Ca/P x PTH) is excellent to specifically recognize PHP or HPT from healthy subjects.